Técnicas de eficiência energética aplicadas ao protocolo fte-leach em ns-3 - Souza, José Ewerton da Cruz de (Universidade Federal Rural do Semi-Árido, 2017)
This research presents a study on energy efficiency techniques and the Fault-tolerant and Energyefficient LEACH (FTE-LEACH) routing protocol in Wireless Sensor Networks (WSN). In order to ensure interoperability among the various devices of a WSN, the Institute of Electrical and Electronics Engineers (IEEE) has developed the IEEE 802.15.4 pattern, which provides a set of new rules for the physical and data link layers according to the OSI Layer Model. The IEEE802.15.4 pattern allows the user to define network and application layers. In this sense, several researches were developed, generating new protocols. Among them, there are the protocols that search for energy efficiency, such as the Low Energy Adaptive Clustering Hierarchy (LEACH) and the Fault-tolerant and Energy-efficient LEACH (FTE-LEACH). In the accomplished study a Simulation Module in Network Simulation 3 (NS-3) was developed, which allowed evaluating the impacts on the energy consumption that the FTE-LEACH protocol promotes in the WSN. The contributions of this research consist in the creation of the Module in NS-3; the construction and presentation of packages and types of messages; the FTE-LEACH protocol encapsulation on the WirelessHART (data link layer); the adoption of 16 (sixteen) channels which are available in the IEEE 802.15.4 pattern; the increase of the dependability weighted by energy efficiency; the centralized election of Cluster Head (CH) without adding new packages to the network; the more accurate tests and results obtained through NS-3; use of TDMA technology at all the stages of the protocol and also the packet parallelism in intracluster communication when different channels are used. Besides these contributions, this research shows, that it is still possible to improve the DE-LEACH protocol, through the use of fuzzy logic, energy consumption balancing techniques as well as broadcast implementation in the adopted WirelessHART TDMA
Keywords: Redes de Sensores Sem Fio (RSSI); Eficiência Energética; Network Simulator 3 (NS-3); Low Energy Adaptive Clustering Hierarchy (LEACH); Fault-tolerant and Energyefficient Low Energy Adaptive Clustering Hierarchy (FTE-LEACH); Wireless Sensor Networks (WSN); Energy Efficiency; Network Simulator 3 (NS-3); Low Energy Adaptive Clustering Hierarchy (LEACH); Fault-tolerant and Energy-efficient Low Energy Adaptive Clustering Hierarchy (FTE-LEACH); CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO